SAT0451 Methotrexate Therapy may Prevent the Onset of Uveitis in Juvenile Idiopathic Arthritis. (23rd January 2014) - Papadopoulou, C.; Kostik, M.; Böhm, M.; Nieto-Gonzalez, J. C.; Gonzalez-Fernandez, M. I.; Gallo, M. C.; Calandra, S.; Consolaro, A.; Martini, A.; Ravelli, A.
Abstract : Objectives: To evaluate whether early treatment with methotrexate (MTX) prevents the onset of uveitis in children with juvenile idiopathic arthritis (JIA). Methods: The clinical charts of all consecutive patients seen between January 2002 and February 2011 who had a disease duration < 1 year at first visit and had received a stable management for at least 2 years with or without MTX were reviewed. Patients who were given systemic medications other than MTX (except NSAIDs) were excluded. Patients with systemic arthritis, rheumatoid factor-positive arthritis, or enthesitis-related arthritis were also excluded. Other exclusion criteria were the development of uveitis before onset of arthritis or before first observation at study center, or the presence of active uveitis at first visit. MTX was administered at 15 mg/m 2 /week (maximum 25 mg/week) in all patients. In each patient, the 2-year follow-up period after first visit was examined to establish whether uveitis had or had not occurred. Results: A total of 254 patients with a median disease duration at first visit of 0.3 years were included. As many as 91.6% of patients were ANA-positive. Eighty-six (33.9%) patients were treated with MTX, whereas 168 (66.1%) patients did not receive MTX. During the 2-year follow-up, 211 (83.1%) patients did not develop uveitis, whereas 43 (16.9%) patients had uveitis, which was diagnosed a median of 1.0 year after first visit. The frequency of uveitis was lower in patients who were given MTX than in patients who did not receive this medication (10.5% vs. 20.2%, respectively; p = 0.049). Survival analysis confirmed that patients treated with MTX had a lower probability of developing uveitis. Conclusions: Early MTX therapy may prevent the onset of uveitis in children with JIA. The potential of MTX to reduce the incidence of ocular disease should be investigated in a randomized controlled trial. Disclosure of Interest: None Declared